Justification of phytoremediation technology of degraded landscapes on the basis of ecosystem approach - Kovrov, Oleksandr; Fedotov, Vyacheslav; Zvoryhin, Kyrylo (Technology audit and production reserves, 2019)
The object of research is the development of natural and survival of artificial plant communities on the surface of the waste dump of the liquidated “Selydivska” coal mine of the State Enterprise “Selydivvugillya” (SE “Selydivvugillya”, Selydove, Ukraine). Phytoremediation of degraded mining lands, in particular rock dumps, aimed at creating a sustainable vegetation cover on the surface of technogenic rock masses. The biggest problem of the biological stage of landfill reclamation is the correct selection of the assortment of trees and shrubs and the creation of plant communities that are resistant to prolonged exposure to toxic substances of rock massifs. Self-breeding of waste dumps continues during their operation, and the dominant species are plants typical of the steppe and forest-steppe zones. The identification of dominant vegetation species on the surface of rock dumps is a source of important information for substantiating targeted phytoremediation of mining landscapes. During 1996-2016 the plant diversity of the waste dump was investigated. It was established that plant groups are predominantly represented by the families of Cereals, Legumes, Asteraceae, and Cruciferous, and the largest number of species is observed along the lower base of the dump and at the top. The expediency of applying the method of phytoremediation of technogenic slopes of waste dumps with sod mats as an alternative environmental technology to restore the mining landscape to the state of the natural ecosystem is substantiated. According to the results of field studies, the survival rate of sod mats on the upper and lower tiers of the surface of the dump is the highest and makes up 53% and 34% of the total number of planted samples of plant communities. The proposed method for phytoremediation of slopes of waste dumps with sod mats with vegetation typical of the selected area is a promising area for accelerated phytoremediation of mining lands.